Prescription Patterns of Antihypertensive Drugs and Adherence to Joint National Committee (Jnc-8) Guidelines in a Tertiary Care Hospital (The Planet, 2021)
Background: Hypertension continues to be an important public health concern because of its associated morbidity, mortality and economic impact on the society. The standard treatment guidelines and drug utilization studies at regular intervals help physicians to prescribe drugs rationally. The adherence of physicians to guidelines is a key issue in the success of therapy and avoidance of serious health complications. Objectives: The purpose of the study was to assess the antihypertensive drug use patterns and adherence to Joint national committee (JNC- 8) hypertension treatment recommendations among newly diagnosed hypertensive patients attending Medicine OPD of Sher- E- Bangla Medical College Hospital, Barishal. Methodology: This cross-sectional study was conducted for a period of one year (July 2016 to June 2017) in the Department of Pharmacology and Therapeutics, Sher-E-Bangla Medical College in collaboration with Medicine OPD of Sher-E-Bangla Medical College Hospital, Barisal. A prescription based survey was conducted among the patients with established hypertension those were registered in the Medicine out patient department of SBMCH, Barishal during the study period. Data were collected from patient’s prescription as well as patients’ interviews. An informed consent was taken from patients participating in the study. Results: A total of 250prescriptions were collected and analysed during study period. The results of this study suggests that study subjects with the age group of 40 to 60 years are most commonly suffering from hypertension. Mean systolic BP of the study subjects was 157.52 ± 7.23 mm of Hg and mean diastolic BP of the study subjects was 96.96 ± 4.90 mm of Hg. Most of the study subjects had no Co-morbidities. Only few study subjects had DM, IHD, Respiratory problem, and Arthritis. DM was the most prevalent co-morbid condition. In this study 38.7% study subjects was treated with Beta blockers (BBs), followed by 33.6% treated with Angiotensin-II receptor blockers (ARBs) and 19.7% with Calcium channel blockers (CCBs). On the other hand in case of combination therapy, TZ+ARB was taken by 47.8% study subjects, followed by 32.7% with CCB+BB and 19.5% with ARB+CCB respectively. The drug adherence in different stages of hypertension was recorded. No adherence in stage I and II were 23(57.5%) cases and 104(49.5%) cases respectively. Adherence was found in 17(42.5%) cases and 106(50.5%) cases in stage I and II respectively. It has been found that significant adherence in stage II HTN and non-adherence in stage I HTN. Conclusion: Adherence of antihypertensive drugs in the stage II hypertension is comparatively better though it is poor in stage I hypertension.
Keywords: Hypertension; Antihypertensive drugs; Prescription pattern; Adherence; Joint national committee-8